Specjalne Strefy Ekonomiczne jako stymulator napływu inwestycji japońskich do Polski - Drelich-Skulska, Bogusława (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Special economic areas in Poland are still very attractive for investors. In 14 areas, currently operating, there are 429 enterprises that invested almost 20 billion PLN and employed 77.600 persons. Poland's accession to the European Union opened the Polish economy for European and Asian investment. The article presents how the specific regulations of special economic areas help the Japanese capital to flow into Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 126-141